Producing users online: Facebook, habit, power - Docherty, Niall (2020)
This thesis examines the scripting (Akrich, 1992) of Facebook’s News Feed with ideal modes of usage, gathering discursive data through Facebook’s PR materials, how-to-guides, and funded academic research, alongside a material analysis of the News Feed’s “choice architecture” (Thaler & Sunstein, 2008) to do so. This empirical analysis is combined with qualitative data gleaned from interviews with users as they scroll down the News Feed, exploring how its technical scripting becomes incorporated in the social networking habits of actual users. The thesis adopts a relational concept of habit informed by John Dewey (1930) and Foucault (1995) to explicate this data, arguing that quotidian, repeated News Feed activity is a learnt practice that entwines the social lives of users with contemporary relations of platform capitalism (Srnicek, 2017). I argue that users are ‘made’ through their repeated activity on the News Feed, and question the extent to which Facebook can be considered as a technology of power as a result – understood as a socio-technical network of relations that prompts certain behaviours, affects and social relations at the expense of others. Through this discussion, the contemporary politics of social media apparatuses are located and explored on the relational level of social norms and governance through habit (Foucault, 1986, 2015; Pedwell, 2017). The approach advanced in this PhD offers fresh insights into the way datafication (Van Dijk, 2014) practices are generated and channelled through the micro-actions of localized users. Thus, the neutrality of Facebook as a ‘tool’ for human usage is challenged, suggesting a more nuanced approach to how we conceptualize the production of patterned usership of social media platforms today.